Research on duplex underwater wireless laser communication system - Dong, Bing; Tong, Shoufeng; Zhang, Peng; Du, Yangfan (Frontiers in Physics, 2023)
To improve the bit error rate (BER) of underwater wireless laser communication and increase communication speed, a duplex underwater wireless laser communication system is designed. The system uses both blue and green lasers to transmit signals simultaneously, and adopts an improved modulation and demodulation algorithm to achieve separate modulation of the two sets of signals. A duplex underwater wireless laser communication system builds based on 440 nm and 550 nm lasers. On the basis of analyzing the absorption and scattering characteristics of seawater in laser communication, the influence of turbulence on communication efficiency is discussed. Improved the traditional duplex modulation algorithm and conducted communication testing at a depth of 2.0m underwater. The experimental results show that when the communication distance increases from 5m to 50m, the BER of the unoptimized duplex mode increases from 2.34 10 -7 to 3.5 10 -5 . After adopting the optimization algorithm, the error rate increases from 2.81 10 -7 to 1.18 10 -6 , and the signal attenuation has been significantly suppressed. The duplex communication structure and algorithm can effectively reduce the impact of communication distance on bit error rate.